The proximity of a field plot and land-use choice: implications for land consolidation - Grammatikopoulou, Ioanna; Myyrä, Sami; Pouta, Eija (ch, 2011)
Traditional methods in agricultural economics and agricultural engineering have yielded mixed results when specifying the costs of an unfavourable parcel structure. Concepts related to travel costs and the production function are frequently applied when the costs of farming distant parcels are examined. However, farmers perspective regarding preferences for land use is ignored or partly overlapped by predictions made by researchers. Based on applied econometric models fitted to stated preference data, we revealed that the proximity of a field plot is a relevant factor affecting land-use decisions. One-fourth of landowners would change the use of a field plot if the condition of distance was changed. Landowners would continue farming a field plot if its distance from the farm compound was reduced, being willing to accept on average 79 less in net income per ha per year. The effect of a greater proximity of field plots to the farm compound following land consolidation was heterogeneous, particularly depending on the farm size and its location.
Keywords: Ma; maankäyttö; maankäytön suunnittelu; land use; land use planning; land use options; distance factor; land consolidation; choice experiment